1998
DOI: 10.1007/s100960050164
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Improved Outcome of Pseudomonas aeruginosa Bacteremia in a Finnish University Hospital

Abstract: All 134 episodes of bacteremia caused solely by Pseudomonas aeruginosa in a university hospital in the periods 1976-1982 and 1992-1996 were reviewed retrospectively to determine the clinical manifestations, outcome and prognostic factors. The mortality for the 30-day interval after drawing the first positive blood culture was 41%, but dropped from 53% in the first period to 29% in the second period (P=0.006). Mortality was highest in patients treated with an aminoglycoside only, as against those treated with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 26 publications
4
61
0
1
Order By: Relevance
“…However, the present study, like other large series from the literature underlined the importance of nosocomial acquisition [2,[4][5][6][7][8][9][10][11]: 88% of our patients developed the infection in hospital. As in other series [3,4,11], preceding procedures and therapies were common in the patients in the present study, and are indicative of the number and severity of concomitant illnesses seen in these patients.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, the present study, like other large series from the literature underlined the importance of nosocomial acquisition [2,[4][5][6][7][8][9][10][11]: 88% of our patients developed the infection in hospital. As in other series [3,4,11], preceding procedures and therapies were common in the patients in the present study, and are indicative of the number and severity of concomitant illnesses seen in these patients.…”
Section: Discussionsupporting
confidence: 62%
“…It is frequently hospital-acquired and may be polymicrobial in nature [1,2]. Despite all the advances in medical practice in recent years, pseudomonal bacteraemia continues to have a high associated mortality, ranging from 18% to 61% [2][3][4][5][6][7][8][9][10][11]. Therefore, investigators have attempted to define those factors that influence the outcome of this infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors that predict a fatal outcome vary among studies and include septic shock, pneumonia, advanced age, severity of the underlying disease, use of inappropriate antimicrobials and emergence of antimicrobial resistance during treatment [7][8][9][10][11]. Rello et al [12] estimated a mortality rate of 13.5% attributable to pneumonia associated with mechanical ventilation caused by P. aeruginosa.…”
mentioning
confidence: 99%
“…Hanna and colleagues [66] showed that documented CRBSIs caused by Gram-negative bacilli were associated with a high frequency of relapse if the CVC was retained. Similarly, with P. aeruginosa CVC sepsis catheter removal also improved patient outcome [67]. Failure to remove the catheter was associated with a significantly higher rate of treatment failure and bacteraemia recurrence (P <0001).…”
Section: Gram-negative Bacillimentioning
confidence: 89%